2015
DOI: 10.1007/s11430-015-5091-9
|View full text |Cite
|
Sign up to set email alerts
|

The potential connection between China surface air temperature and the Atlantic Multidecadal Oscillation (AMO) in the Pre-industrial Period

Abstract: One recent study by using instrumental records suggested the correlation between East Asian surface air temperatures (EATs) and the Atlantic Multidecadal Oscillation (AMO) reaches the maximum when the former leads the latter by 5-7 years. This seems to disagree with a previous well-realized point that the AMO modulates the decadal variation of EATs, since the atmosphere responds swiftly to sea surface temperature anomalies (SSTA) if therein. It implies that the AMO-EATs correlation should reach the maximum whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…The relationships between precipitation over East Asia and large-scale climate patterns, such as the El Niño Southern Oscillation (ENSO), North Atlantic Oscillation (NAO), Pacific Decadal Oscillation (PDO), and Atlantic Multi-decadal Oscillation (AMO), were identified through the influence of atmospheric circulation [10][11][12][13][14]. However, the underlying dynamics are various for these teleconnections of climate patterns and the seasonal precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…The relationships between precipitation over East Asia and large-scale climate patterns, such as the El Niño Southern Oscillation (ENSO), North Atlantic Oscillation (NAO), Pacific Decadal Oscillation (PDO), and Atlantic Multi-decadal Oscillation (AMO), were identified through the influence of atmospheric circulation [10][11][12][13][14]. However, the underlying dynamics are various for these teleconnections of climate patterns and the seasonal precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…the North Atlantic SST tripole and the Atlantic Multidecadal Oscillation), as well as the related patterns of atmospheric circulation anomalies, such as the North Atlantic Oscillation (NAO) and Arctic Oscillation, are closely linked to climate anomalies in adjacent Europe, North and South America, and Africa, on different timescales (Uvo et al ., ; McHugh and Rogers, ; Sutton and Hodson, , ; Kushnir et al ., ; Nnamchi and Li, ; Sutton and Dong, ; Amorim et al ., ; Myoung et al ., ). Moreover, the SST and atmospheric circulation anomalies in the Atlantic Ocean can remotely affect Asian circulations and associated precipitation and temperature anomalies (Goswami et al ., ; Lu et al ., ; Sung et al ., ; Li and Bates, ; Li et al ., , , ; Wu et al ., , , ; Sun, , ; Zuo et al ., ; Chen et al ., ). Wu et al .…”
Section: Introductionmentioning
confidence: 99%
“…the North Atlantic SST tripole and the Atlantic Multidecadal Oscillation), as well as the related patterns of atmospheric circulation anomalies, such as the North Atlantic Oscillation (NAO) and Arctic Oscillation, are closely linked to climate anomalies in adjacent Europe, North and South America, and Africa, on different timescales (Uvo et al, 1998;McHugh and Rogers, 2001;Hodson, 2005, 2007;Kushnir et al, 2010;Nnamchi and Li, 2011;Sutton and Dong, 2012;Amorim et al, 2014;Myoung et al, 2015). Moreover, the SST and atmospheric circulation anomalies in the Atlantic Ocean can remotely affect Asian circulations and associated precipitation and temperature anomalies (Goswami et al, 2006;Lu et al, 2006;Sung et al, 2006;Li and Bates, 2007;Li et al, 2008aLi et al, , 2008bLi et al, , 2015Wu et al, 2009cWu et al, , 2010aWu et al, , 2010bSun, 2012Sun, , 2014Zuo et al, 2013;Chen et al, 2015). Wu et al (2009c) suggested that an anomalous NAO in boreal spring can induce a tripole SST anomaly pattern in the North Atlantic, persisting into the ensuing summer and stimulating atmospheric teleconnection affecting the East Asian summer monsoon.…”
Section: Introductionmentioning
confidence: 99%
“…The 2.75-4-year cycle could be associated with the El Niño Southern Oscillation (ENSO), which has a frequency of about 3-8 years [83]. The 40-65-year climate cycle may be related to the North Atlantic Oscillation (NAO) [84] or to the Atlantic Multidecadal Oscillation (AMO) [85]. As discussed in previous studies, these climatic cycles have a major impact on the regional climate of Nepal [24,26,36,86].…”
Section: Long-term Trend In Spring Temperature and Teleconnectionsmentioning
confidence: 90%
“…Previous studies found that a positive AMO mode extends the duration of the summer monsoon in the southeast and east Asia [87]. Li et al [85] claimed that the East Asian temperature leads to the occurrence of the positive AMO phase, which creates a positive relationship with temperature and AMO. The effect of the positive NAO index is negative on spring temperature (favoring growth) in our study area.…”
Section: Long-term Trend In Spring Temperature and Teleconnectionsmentioning
confidence: 98%